Pengaruh Penggunaan Media Ular Tangga terhadap Kemampuan Mengenal Lambang Bilangan Anak Usia 5-6 - Bungaria Febryani Simanjuntak; Rotua Samosir; Uranus Zamili (Pusat Riset dan Inovasi Nasional, 2023)
Based on the results of the initial observations that the author made at the Mandiri ABCD Kindergarten in Sipoholon District, it shows that the Kindergarten still does not use various interesting media to facilitate learning in the classroom. This research is motivated by problems that arise in class, namely children are less able to recognize number symbols properly because the child's cognitive abilities have not yet emerged, so that the facilities at school to recognize numbers are minimal, as well as the recognition of number symbols is less attractive. The purpose of this study was to determine the effect of using snakes and ladders media on the ability to recognize number symbols for children aged 5-6 years at Mandiri ABCD Kindergarten, Sipoholon District. The method used in this research is descriptive quantitative research method. The population is all children aged 5-6 years in Mandiri ABCD Kindergarten, Sipoholon District, totaling 108 people and a sample of 20 people is determined using a non-probability sampling technique, namely purposive sampling. Data was collected using a closed questionnaire consisting of 23 items. The results of the data analysis showed that there was a positive and significant influence on the use of snakes and ladders media on the ability to recognize number symbols for children aged 5-6 years at Mandiri ABCD Kindergarten, Sipoholon District. Thus Ha is accepted and H0 is reject.